A Flexible Monopole Antenna with Dual-Notched Band Function for Ultrawideband Applications - Xiaoyan Zhang; Guohao Wang (International Journal of Antennas and Propagation)
We present a flexible ultrawideband (UWB) planar monopole antenna with dual-notched band characteristic printed on a polyimide substrate. The antenna is fed by a step coplanar waveguide (CPW) that provides smooth transitional impedance for improved matching. It operates from 2.76 to 10.6 GHz with return loss greater than 10 dB except for the notch band to reduce the interference with existing 3.5 GHz WiMAX band and 5.5 GHz WLAN band. With a combination of rectangular and circle patches in which the U-shaped slot is carved, the overall size of antenna is 30 mm × 20 mm. Moreover, a pair of arc-shaped stubs located at both sides of the feed line is utilized to create the notch band for WiMAX band. The results also show that the antenna has omnidirectional radiation pattern and smooth gain over the entire operational band.